Simultaneous co-hydrothermal carbonization and chemical activation of food wastes to develop hydrochar for aquatic environmental remediation. (March 2022) - Ahmed Alshareef, Shareefa; Abdullah Alqadami, Ayoub; Ali Khan, Moonis; Alanazi, Hamdah S.; Raza Siddiqui, Masoom; Jeon, Byong-Hun
Highlights: ACG and OOC simultaneous Co-HTC and chemical activation to develop HC. Low SSA (2.94 m 2 /g) HC with dominance of oxygen containing functionalities. Dyes adsorption due to hydrogen bonding, electrostatic, and π-π/n-π interactions. In Co range 50 – 200 mg/L, 50 to 90% of MB and CV dyes were removed in 15 min. Elution of CV (58%) and MB (14.8%) dyes were maximum in ethanol. Abstract: Locally generated food wastes, such as Arabic coffee ground (ACG) and olive oil cake (OOC) were converted to N-ACG: OOC – 3 hydrochar (HC) through simultaneous co-hydrothermal carbonization (Co-HTC) and chemical activation. The optimized ACG: OOC mass ratio (g: g) and chemical activation agent used were 1.2: 0.8 and 0.1 M HNO3, respectively. Spectroscopic analyses confirmed the dominance of oxygen-containing functionalities, whereas the X-ray diffraction pattern displayed peaks for both sucrose and cellulose on N-ACG: OOC – 3. The developed HC was tested for methylene blue (MB) and crystal violet (CV) adsorption in aqueous systems. Batch scale adsorption studies showed pH, initial concentration (Co ), time (t), and temperature (T) dependent dye uptake. Maximum dye uptake was observed at pH 7, with 50 – 70% and 76 – 90 % CV and MB removal achieved within 15 min at varied Co : 50 – 200 mg/L. Adsorption was governed by multiple mechanisms, including hydrogen bonding, electrostatic interactions, π–π interactions, and n-π interactions. Dye elution was higher in ethanol (EtOH: C2 H5 OH), and CV elution (50.8%) was more significant than MB elution (14.8%).